Analisis Kepuasan Konsumen Terhadap PT Pegadaian Cabang Palembang Unit Taman Bukit Siguntang - Nelly; Vivin Afini; Putri Adelia Ramadhania (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
The purpose of this research is to determine consumer satisfaction with PT. Pegadaian Palembang Branch Taman Bukit Siguntang Unit. The data used in the research uses primary data and secondary data through interviews, observation, documentation and filling out questionnaires. The sample used in this research uses an incidental sample of 100 respondents from a total population of 1316. The method in this research uses a qualitative descriptive analysis method where the indicators used in this research are: Quick Completion, Completeness of Facilities, Company Reputation and Image, Employee Friendliness, Cleanliness Room, Employee Responsiveness, Understanding Customer Needs, Warranty. Based on the results of customer satisfaction index (IKP) research on PT. Pegadaian Palembang Branch, Taman Bukit Siguntang Unit shows information that the actual performance level is the same as the expected performance level, namely 3.38, which means that PT Pegadaian Palembang Branch, Taman Bukit Siguntang Unit is quite satisfactory to customers. In general, the company's performance has met consumer expectations on several indicators such as quick completion, company reputation and image, cleanliness of the room, understanding customer needs, and guarantee. However, there are several areas that need improvement to increase overall customer satisfaction, such as completeness of facilities,employee friendliness and employee responsiveness.